LIVING EXPERIENCE OF WOMEN WITH HIV/AIDS IN WEST JAVA INDONESIA - Ellya Susilowati; Krisna Dewi (Indonesian Journal of Social Work, 2019)
The purpose of this research is to understand how the experience of women's lives, so that it becomes the basis of social workers in providing help for women with HIV/AIDS. This research used a qualitative method with descriptive design to three women with HIV/AIDS who received services from the Komisi Penanggulangan AIDS/AIDS Prevention Commission in Kerawang Regency, West Java. Data collection techniques used were interviews, observation and documentation studies. The results of the research showed that women experienced changes after contracting HIV/AIDS from: 1) physical aspects experiencing changes in skin color, decreased health conditions; 2) in the psychological aspect it becomes more sensitive and quickly offended; 3) social aspects still experience discrimination from the family, and still cannot negotiate with their husbands regarding condom use; 4) economically, experiencing more expenditure for accessing to health services and purchasing drugs; 5) service aspects still have no partner counseling services and educational activities for the environment so there is still stigma and discrimination. The recommendation for the results of this research is that the Komisi Penanggulangan AIDS/AIDS Prevention Commission: 1) establish a counseling service program for couples; 2) improve support group programs for women; 3) counseling about HIV/AIDS in the family and community environment so as not to stigmatize and discriminate against women with HIV/AIDS.